Memorandum on the Beveridge Report - Beveridge, William Henry Beveridge, Baron, 1879-1963 (London : Communist Party of Great Britain)
1943-02 1943 1940s 28 pages to spend more of his subsistence benefit in rent and less in food than would the citizens in other parts of the country. The ultimate solution is the reduction of the excessively high London rents. We believe, however, that the immediate solution should be the supplementing of the subsistence benefits in the case of those who have high rents to pay. The method we suggest is as follows:— It should be assumed that in the 50/- subsistence allowance for a married couple there is 12/- allowed for rent. Anyone who is in fact paying a higher rent could apply for supplementation. A similar procedure could be followed in the case of the single man or woman whose subsistence benefit could be assumed to carry a rent allowance of 8/2. A substantial number of workers are now purchasing their houses from building societies by means of weekly instalments ranging from £1 to £1 15s. per week. Obviously the workers could not meet such obligations out of their subsistence benefit and would, therefore, be subject to pressure of the building societies because they were not paying the weekly sums laid down in the contract. We think that the worker should be called to pay only the sum allowed for rent in the subsistence scale, namely 12/- per week when sick or unemployed, and that the building society should not be allowed to press him for arrears when he becomes employed again. The effect of this would simply be to spread the purchase of the house over a greater number of years, and would not inflict any great burden on the building society. It would end the scandal of workers who have paid for such houses being forced to sell out their rights during periods of unemployment and sickness. WIDOW'S PENSIONS After guaranteeing existing widows their 10/- unconditional pension, the Beveridge scheme lays it down that in future no widow shall receive an unconditional widow's pension for life. 15 15X/2/103/272